Analysis of Amplify-and-Forward Cooperative Networks with Nakagami-m fading Channels For MRC Diversity Combining - Ali Abdulwahhab Mohammed; Li Yu; Manar Al-Kali; Desheng Wang (Institute of Advanced Engineering and Science, 2015)
In this paper we study the effect of diversity combining for Nakagami -m fading Channels in the amplify-and-forward cooperative networks.We derive the cumulative density function (CDF), probability density function (PDF) and moment generating function (MGF) for the multiple relay amplify-and-forward network with single half duplex channel maximal ratio combiner (MRC). In this network we investigate the cases of MRC at the destination, as well derive the exact Symbol Error Rate (SER) of M-ary phase-shift keying (M-PSK), and quadrature amplitude modulation (M-QAM) in Nakagami -m fading environment. We present a comparison between M-PSK and M-QAM modulation schemes in some representative scenarios where an arbitrary number of cooperative relays is considered.